Performance of food–feed maize and cowpea cultivars under monoculture and intercropping systems: Grain yield, fodder biomass, and nutritive value - Sanfo, Abroulaye; Zampaligré, Nouhoun; Kulo, Abalo E.; Somé, Sanyour; Traoré, Kadiatou; Rios, Esteban F.; Dubeux, José C. B.; Boote, Kenneth J.; Adesogan, Adegbola (Frontiers in Animal Science, 2023)
Livestock feeding in Burkina Faso is characterized by recurrent dry season fodder deficit both in quality and quantity, which affect animal performance. To overcome this situation, quality fodder/forage production is an alternative. Hence, this study evaluated food-feed improved cultivars of maize and cowpea in intercropping trials using “Mother and Baby trials" approach with crop-livestock farmers. The mother trial was a completely randomized block design with eight treatments and four replications: two cowpeas and two maize cultivars, grown under two cropping systems: monoculture and intercropping. Baby trials were established on-farm and involved 30 farmers during two seasons (2019 and 2020) in four villages in the South Sudan zone in Burkina Faso. Data were collected on (i) weed density and biomass, (ii) grain yield and fodder biomass, (iii) intercropping efficiency, and (iv) fodder nutritive value. Data were analyzed using ANOVA and LSD means separation at 5% threshold. The results revealed that maize and cowpea intercropping significantly reduced weed biomass (p≤0.05). In monoculture, maize cultivar Barka produced greater grain yield (4980 kg/ha) and fodder biomass (6259 kg DM/ha) than cultivar Espoir, which produced 2581 kg/ha grain yield and 4952 kg DM/ha fodder biomass. Cowpea cultivars KVx745-11P and Tiligré were similar (p≥0.05) for fodder biomass (2435-2820 kg DM/ha) and grain yield (1152-1163 kg/ha). Land Equivalent Ratios for fodder biomass (1.18-1.41) and grain yield (1.02-1.44) under intercropping were greater than 1 with better Productivity System Indexes compared with monocultures. The fodder crude protein concentration (9.5-9.8%) was greater for Barka than Espoir (8.5-8.7%). The crude protein of KVx745-11P (19-21.8%) was greater than of Tiligré (15-17%). Intercropping maize Barka and cowpea KVx745-11P was the most productive cropping system for maximizing grain and fodder production for crop-livestock farmers in the South Sudan zone in Burkina Faso.